Qualitative accounting research: dispelling myths and developing a new research agenda. (30th May 2019) - de Villiers, Charl; Dumay, John; Maroun, Warren
Abstract: This article deals with some common misconceptions about qualitative research. Qualitative studies are well suited to studying complex interconnections and relationships without reducing the complexity to simple numbers or variables. Rather than excluding outliers from a dataset, qualitative researchers are interested in these exceptions and often examine them in‐depth in order to develop better understandings and generate new theories on how accounting develops, functions and influences behaviour. New understandings and theory allow qualitative research to advance recommendations, extend the boundaries of accounting research, and make important contributions to both accounting theory and practice.